Influence of Nurses’ and Teachers’ Roles in Health Education on Dengue Prevention Behavior Changes in Schools - Rustam Aji Rochmat; Dewi Lusiani; Tonny Cortis Maigoda; Wiwiek Mulyani; Darwis; Indah Fitri Andini; Sherly Ratih Frichesyarius Santi Ajhie; Roro Ajhie Ayuningtyas (Journal of Applied Holistic Nursing Science, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a major public health problem in tropical regions, including Indonesia, due to high morbidity rates and environmental factors that support mosquito breeding. This study aimed to determine the influence of nurses and teachers in health education on changes in dengue prevention behavior in schools. Methods: This research used a single-group pretest-posttest experimental design with 90 respondents selected purposively. Changes in knowledge and behavior were assessed before and after the intervention. The intervention involved health education on dengue prevention, focusing on the 3M Plus method: draining, covering, recycling, and using larvicide. Results: The results showed a significant increase in the proportion of respondents with good preventive behavior, rising from 15.6% in the pretest to 91.1% in the posttest (p-value = 0.000). This indicates that health education significantly improves public knowledge and encourages positive behavioral changes in dengue prevention. Conclusion: Health education significantly improves dengue prevention behavior, raising good practices from 15.6% to 91.1%. Sustained community involvement and policy support are crucial for lasting impact.